Factors influencing the production of volatile phenols by wine lactic acid bacteria - Silva, Isa (2012)
This work aimed to evaluate the effect of certain factors on the production of volatile phenols from the metabolism of p-coumaric acid by lactic acid bacteria (LAB) (Lactobacillus plantarum, L. collinoides and Pediococcus pentosaceus). The studied factors were: pH, L-malic acid concentration, glucose and fructose concentrations and aerobic/anaerobic conditions. It was found that, in the pH range of 3.5 to 4.5, the higher the pH the greater the production of volatile phenols. This behaviour is correlated with the effect of pH on bacterial growth. Increasing levels of L-malic acid in the medium diminished the production of 4-vinylphenol (4VP) and stimulated the production of 4-ethylphenol (4EP) by L. plantarum NCFB 1752 and L. collinoides ESB 99. The conversion of 4VP into 4EP by the activity of the vinylphenol reductase may be advantageous to the cells in the presence of L-malic acid, presumably due to the generation of NAD(+), a cofactor required by the malolactic enzyme. Relatively high levels of glucose (20 g/L) led to an almost exclusive production of 4VP by L. plantarum NCFB 1752, while at low concentrations (<= 5 g/L), 4EP is mainly or solely produced. Part of the glucose may be diverted to the production of mannitol as an alternative pathway to regenerate NAD+. This is corroborated by the experiments done with fructose, a compound that can be used as an electron acceptor by some bacteria becoming reduced to mannitol. In anaerobiosis, the reduction of 4VP into 4EP is clearly favoured, which is consistent with the need to increase the availability of NAD(+) in these conditions. This study shows that the amount and the ratio 4VP/4EP produced by LAB are greatly affected by certain environmental and medium composition factors. The behaviour of the bacteria seems to be driven by the intracellular NAD(+)/NADH balance.